Prematurity: A Major Cause of Early Neonatal Mortality in Ad-din Medical College Hospital (Bangladesh Journal of Medical Science, 2019)
Objective: Early neonatal mortality within the ﬁ rst 24 hours contributes substantially to overall neonatal mortality rates. Reliable cause- specific mortality data are limited; thus the estimated proportion of prematurity-related deaths nationally remains questionable. The objective was to determine the presumed causes of neonatal death within the ﬁ rst 24 hours in Ad-din Medical College Hospital.Methods: This is a retrospective study initiated in January of 2016 to December 2016, conducted in the delivery room and adjacent neonatal area at Ad-din Medical College Hospital. Research assistants were trained to observe and record events related to labor, neonatal resuscitation, and 24-hour postnatal course. Perinatal asphyxia (PNA) was defined as failure to initiate spontaneous respirations and/or 5-minute Apgar score